Empowering local economic potential post COVID-19 pandemic - Siti Ridloah; Desti Ranihusna; Vini Wiratno Putri; Vitradesie Noekent; Nury Ariani Wulansari (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2024)
Karanganyar Regency still has 25 villages in five sub-districts that are categorized as extremely poor. This condition has an impact on the high unemployment rate (5.70%) and the percentage of the population who are no longer in school (72.21%), coupled with the COVID-19 pandemic which has an increasing impact on people's low incomes. This service activity aims to develop productive economic empowerment for households to mitigate poverty due to the COVID-19 pandemic in Jatisari District, Karanganyar Regency. Methods for implementing activities include a preliminary study of problems, brainstorming with partners, training, and post-activity assistance with the Dasa Wisma women's group and local MSMEs. The training includes knowledge about village potential maps, entrepreneurial motivation, training on creating products with local wisdom potential, and assistance in packaging superior village products. This activity had a positive impact in increasing community awareness by 90% of the need to improve their economic conditions and 64% of participants after participating in the activity had business ideas to try opportunities for developing local village potential products. This activity can significantly improve the economy of the target community by empowering the household economy based on local village potential.